2006
DOI: 10.1007/s00595-006-3319-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model of Stage II Non-Small Cell Lung Cancer by a Discriminant Analysis of the Immunohistochemical Protein Expression

Abstract: A discriminant analysis is thus considered to be a useful statistical method for analyzing the protein expression profiles obtained by combined TMA and immunohistochemical techniques using archival NSCLC tissues. However, the sample size and selection of the marker protein depending on the histology greatly influence the results of a NSCLC study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…Studies have shown that the discriminant analysis has been clinically used to select significant indicators 18‐20 . In this work, we first applied this analysis to establish a predictive model to screen the major factors of prognosis in patients with aSAH, which may be availably applied in clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the discriminant analysis has been clinically used to select significant indicators 18‐20 . In this work, we first applied this analysis to establish a predictive model to screen the major factors of prognosis in patients with aSAH, which may be availably applied in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the discriminant analysis has been clinically used to select significant indicators. [18][19][20] In this work, we first applied this analysis to establish a predictive model to screen the major factors of prognosis in patients with aSAH, which may be availably applied in clinic. Our findings from multivariate Logistic analysis showed that the high GCS score 24-hour after surgery Previous studies have demonstrated that NLR was associated with the outcomes and could predict the courses of different medical conditions, such as ischemic stroke, 21,22 cerebral hemorrhage, 23,24 and major cardiac events.…”
Section: F I G U R E 2 Roc Curve Of the Prognosis In Patients With Aashmentioning
confidence: 99%
“…Immunohistochemistry was carried out using avidin–biotin–peroxidase complex as previously reported 9 . A panel of 15 antibodies with previously known prognostic significance was used to evaluate the biological differences among the three histological subgroups and the different tumor cell growth patterns in ADMIX 10 . Information on the 15 antibodies used in the study is summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Η ιστολογική διάγνωση του επιδερμοειδούς καρκινώματος τίθεται επί της παρουσίας κερατίνης η οποία παράγεται από τα κύτταρα του όγκου και/ή από την παρουσία ενδοκυτταρικών δεσμοσωματίων (οι αναφερόμενες ως «ενδοκυτταρικές γέφυρες»). Ορισμένοι όγκοι οι οποίοι έχουν κυρίως ατρακτοειδή εικόνα (τα ατρακτοειδή [194]. Ωστόσο, σε μια πιο πρόσφατη μελέτη η οποία αφορά ασθενείς με NSCLC σταδίου IB-IIIA, καμία σημαντική συσχέτιση μεταξύ της έκφρασης του RCAS1 και των παραμέτρων επιβίωσης (OS, PFS) δεν παρατηρήθηκε [195].…”
Section: προληπτικος ελεγχος καρκινου πνευμοναunclassified
“…-113 - [194]. Ωστόσο, σε μια πιο πρόσφατη μελέτη η οποία αφορούσε ασθενείς με NSCLC σταδίου IB-IIIA, δεν παρατηρήθηκε καμία σημαντική συσχέτιση μεταξύ της έκφρασης του RCAS1 και των παραμέτρων επιβίωσης (OS, PFS) [195].…”
Section: δεικτης κυτταρικου πολλαπλασιασμου Ki-67unclassified